Assessments of students’ gains in conceptual understanding and technical skills after using authentic, online learning modules on hydrology and water resources - Byrd, Jenny; Gallagher, Melissa A.; Habib, Emad (Frontiers in Education, 2022)
The need to adapt quickly to online or remote instruction has been a challenge for instructors during the COVID pandemic. A common issue instructors face is finding high-quality curricular materials that can enhance student learning by engaging them in solving complex, real-world problems. The current study evaluates a set of 15 web-based learning modules that promote the use of authentic, high-cognitive demand tasks. The modules were developed collaboratively by a group of instructors during a HydroLearn hackathon-workshop program. The modules cover various topics in hydrology and water resources, including physical hydrology, hydraulics, climate change, groundwater flow and quality, fluid mechanics, open channel flow, remote sensing, frequency analysis, data science, and evapotranspiration. The study evaluates the impact of the modules on students’ learning in terms of two primary aspects: understanding of fundamental concepts and improving technical skills. The study uses a practical instrument to measure students’ perceived changes in concepts and technical skills known as the Student Assessment of Learning Gains (SALG) survey. The survey was used at two-time points in this study: before the students participated in the module (pre) and at the conclusion of the module (post). The surveys were modified to capture the concepts and skills aligned with the learning objectives of each module. We calculated the learning gains by examining differences in students' self-reported understanding of concepts and skills from pre- to post-implementation on the SALG using paired samples t-tests. The majority of the findings were statistically at the 0.05 level and practically significant. As measured by effect size, practical significance is a means for identifying the strength of the conclusions about a group of differences or the relationship between variables in a study. The average effect size in educational research is d = 0.4. The effect sizes from this study [0.45, 1.54] suggest that the modules play an important role in supporting students' gains in conceptual understanding and technical skills. The evidence from this study suggests that these learning modules can be a promising way to deliver complex subjects to students in a timely and effective manner.